Age Estimation among Adolescent Individuals from Fusion of Tri-Radiate Cartilage: A Radiological Study from Central India - Ninad Nagrale1 , Swapnil Patond2 , Ranjit Ambad3 , Nandkishor Bankar3 , Karan Jain4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Age determination in living individuals, dead persons & in human remains may shed light on issues withnotable legal and social consequences for individuals as well as for the community. In the age determinationof the deceased individual; the post-mortem circumstances can change the body parts and make ageestimation difficult. In such cases, skeletal remains are extremely helpful for age determination. This studyfocuses on investigating the relationship between the stage of fusion of tri-radiate cartilage of innominatebone & biological age in population of Central India. This study was carried out in 120 healthy subjects (60males and 60 females) aging from 12 to 18 years. The obtained results revealed that the complete fusion oftri-radiate cartilageis seen at 16-17 years. Comparatively, females were developing union at a younger agethan their male counterparts. Results also suggest that the age of fusion of tri-radiate cartilage is found tovary greatly all over the India & world, indicating the need for separate standards for separate regions.